Potential Use of Bisphosphonates in Invasive Extramammary Paget’s Disease: An Immunohistochemical Investigation - Taku Fujimura; Sadanori Furudate; Yumi Kambayashi; Setsuya Aiba (Clinical and Developmental Immunology)
Invasive extramammary Paget’s disease (EMPD) is relatively rare and is reported to be highly metastatic to lymph nodes or even other organs, including bone. Histologically, EMPD shows significant numbers of lymphocytes around the tumor mass, suggesting the possible development of novel immunomodulatory therapy for EMPD by targeting these infiltrating lymphocytes. Previously, bisphosphonates (BPs) were administered for the treatment of malignancy, especially osteolytic bone disease. Recent reports also suggested that BPs might have a direct antitumor effect through several pathways beyond their beneficial effect on bone metastasis. Among them, the abrogation of immunosuppressive cells, myeloid derived suppressor cells (MDSC), by BPs might be one of the optimal methods to induce an antitumor immune response both locally and at sites remote from the tumor. In this study, we employed immunohistochemical staining for immunosuppressive macrophages and cytotoxic T cells in the lesional skin of patients with noninvasive EMPD and those with invasive EMPD.